Efficacy of Luliconazole Against Broad-Range Filamentous Fungi Including Fusarium solani Species Complex Causing Fungal Keratitis. Issue 2 (February 2019) - Todokoro, Daisuke; Suzuki, Takashi; Tamura, Takashi; Makimura, Koichi; Yamaguchi, Hideyo; Inagaki, Katsuhiro; Akiyama, Hideo
Abstract : Purpose: Fungal keratitis can be difficult to medically treat. Topical antifungals are usually applied empirically as the initial option in treating fungal keratitis. Natamycin (NAT) and/or voriconazole (VRCZ) have been widely used in the treatment of fungal keratitis. However, Fusarium solani species complex (FSSC), which are the dominant species of fungal keratitis, are resistant to VRCZ. This study investigated in vitro efficacy of luliconazole (LLCZ), a new imidazole antifungal, against FSSC and other filamentous fungi. Methods: A total of 18 Fusarium isolates and 7 others were grown on potato dextrose agar at 30 and 37°C. For Fusarium, species identification and phylogenetic tree analysis were performed based on elongation factor-1α (EF-1α) DNA sequencing. The broth microdilution method was used for antifungal susceptibility testing of 11 antifungal drugs including LLCZ. Results: The 18 identified Fusarium isolates belonged to FSSC (n = 13), Fusarium oxysporum species complex (FOSC; n = 2), Fusarium chlamydosporum species complex (FCSC; n = 1), Fusarium incarnatum-equiseti species complex (FIESC; n = 1), and Fusarium fujikuroi species complex (FFSC; n = 1). We further divided 13 FSSC isolates into 3 clades, FSSC5 (n = 8), FSSC3 + 4 (n = 4), and FSSC9-a (n = 1), with 8 FSSC strains growing at 37°C. LLCZ showed lowest minimum inhibitory concentrations (MICs) against all tested filamentous fungi, with a MIC90 against the Fusarium species of 0.06 μg/mL, whereas MIC90 for NAT and VRCZ were 4 and 8 μg/mL, respectively. Conclusions: LLCZ has the strongest in vitro antifungal activity among all drugs used against broad-range filamentous fungi including FSSC. LLCZ may potentially be a new medical treatment option for fungal keratitis.